The effect of flipped classroom on intrinsic motivation and achievement in chemical equilibirum among year 11 pupils / Yong Wei Zhen - Yong , Wei Zhen (2020)
Nowadays, lack of motivation has been quoted as one of the leading challenges in chemistry education. In science education, low academic achievement in chemistry is another major problem encountered in secondary school. Therefore, the purpose of this study was to investigate the effect of flipped classroom on intrinsic motivation and achievement in chemical equilibrium among Year 11 pupils. This study employed a quasi-experimental non-equivalent pretest-posttest design. Sixty (60) Year 11 secondary school chemistry pupils from two intact classes were assigned to an experimental group (n = 30) and a control group (n = 30). The experimental group students were exposed with flipped classroom approach and the control group pupils were exposed with the traditional classroom approach. The research was conducted for six weeks in a secondary chemistry education international school setting. Research instruments used in this study were the modified version of Intrinsic Motivation Inventory (IMI) to evaluate the pupils’ intrinsic motivation based on the indicators of autonomy, competence, relatedness, interest and value; Chemical Equilibrium Achievement Test (CEAT) to measure students’ achievement scores. Reliability and validity of the instruments were assessed in the pilot study. The reliability obtained for IMI, Cronbach’s α is 0.88 and for CEAT, test-retest r is 0.89. The validity coefficients for IMI are acceptable and exceed the acceptable factor loading criterion of 0.35. The analysis of CEAT was validated by three experienced teachers from Cambridge Assessment Specialist Team. Quantitative data were analyzed using Analysis of covariance (ANCOVA) and Pearson Correlation test. The major findings of this study revealed that there was a significant difference between experimental group and control group on pupils’ post intrinsic motivation scores with pretest as a covariate (F (1, 57) = 64.41, p < .05) Also, it showed that there was a significant difference between experimental group and control group on pupils post chemical equilibrium achievement scores with pretest as a covariate (F (1, 57) = 37.38, p < .05). The Pearson Correlation test results revealed that the relationship between pupils’ intrinsic motivation and chemical equilibrium achievement scores in experimental group after intervention was significant: r = .39, p < .05. For intrinsic motivation scores, the experimental group with an average mean of 70.63 scored significantly higher than the control group with an average mean of 61.00. For chemical equilibrium achievement scores, the experimental group with an average mean of 15.3 scored significantly higher than the control group with an average mean of 9.83. The results showed that the flipped classroom approach enhances pupils’ intrinsic motivation as well as achievement in chemical equilibrium. The findings of this study have theoretical significance as well as pedagogical implications. In addition, the findings of this study suggested the importance of flipped classroom approach to improve secondary school pupils’ intrinsic motivation and achievement in chemical equilibrium. This study also helps to inform a better chemistry education learning strategy for pupils and provide suggestions for future research using flipped classroom approach. Therefore, the study recommended that flipped classroom approach should be added to the teaching strategies of chemistry teachers at the secondary school level